The complete mitochondrial genome of Nerita albicilla (Neritimorpha: Neritidae). Issue 1 (2nd January 2019) - Feng, Jiantong; Fu, Zeqin; Guo, Yahong; Ye, Yingying; Li, Jiji; Guo, Baoying; Lü, Zhenming
Abstract: The complete mitochondrial genome of Nerita albicilla was determined. The mitochondrial genome is 15, 314 bp in length, comprising two ribosomal RNA (12S and 16S) genes, 13 protein-coding genes, and 22 transfer RNA genes. Of these 37 genes identified, seven protein-coding genes, and eight transfer RNA genes are encoded on the heavy strand and the other genes on the light strand. This gene order is consistent with the previously published mitochondrial genomes of the other neritid species. The length of 22 tRNAs ranges from 65 bp to 73 bp and the overall base composition is 14.9% of C, 20.7% of G, 34.0% of T, and 30.5% of A. The phylogenetic tree was constructed based on 13 protein-coding genes of N. albicilla and other 13 Archaeogastropoda species, Argopecten purpuratus as outgroup using the Neighbor-joining method, the tree showed that N. albicilla is most closely related to the Nerita yoldii. We believe that this result will further supplement the genome information in mitochondria of the family Neritidae and facilitate the study on population genetic.